Use of quantitative criteria in the management of personal consumption expenditure: challenges and opportunities - Taujanskaitė, Kamilė; Milčius, Eugenijus; Dobrovolskienė, Nomeda (Journal of Business Economics and Management, 2017)
Various non-economic factors, like social, cultural, psychologic and others strongly affect the decision-making related to the management of personal consumption expenditure (PCE) in households and often compromise its efficiency. PCE management tools and methods currently used by households are not helpful either as rational distribution of funds among the purchases is usually out of their scope. Therefore, rational use of resources still remains a challenging task for many households. The goal of this study is to analyse the PCE management process in households and the obstacles preventing its efficiency. Methods used in the article comprise: comparative and critical analysis methods; vector analysis tools. The paper identifies shortcomings of currently used PCE management methods and tools and introduces a system of quantitative criteria enabling objective evaluation of consumption alternatives. The use of quantitative criteria limits the influence of subjective, non-economic factors on consumption-related resource management in households and can positively affect its efficiency. The criteria are justified theoretically and the benefits from their use demonstrated with some practical evidence.